(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To describe the clinical and paraclinical characteristics (X-ray, CT scan) of patients with closed intra-articular distal tibial fractures indicated for locking plate fixation at 108 Military Central Hospital. Subjects and Methods: A cross-sectional descriptive study was conducted on 45 patients with closed intra-articular distal tibial fractures who underwent locking plate fixation at the Department of General Orthopedic Trauma, 108 Military Central Hospital, from January 2022 to June 2025. Results: Local soft tissue injuries (according to the Tscherne classification) were distributed relatively evenly among three grades: grade 1 (28.89%), grade 2 (37.78%), and grade 3 (33.33%). The most common associated injury was traumatic brain injury (11.11%). Hypertension was the most frequent comorbidity (13.33%), followed by cancer (6.67%). According to the AO classification, type B2 fractures were the most prevalent (35.56%), followed by type B3 (28.89%). There were 24 cases of isolated distal tibial fractures and 21 cases with concomitant fibular fractures. Bilateral column involvement accounted for the majority, with 22 cases (48.89%). Conclusion: Patients with closed intra-articular distal tibial fractures frequently presented with local soft tissue injuries (Tscherne), were prone to associated injuries, often had concomitant fibular fractures, and exhibited multi-column involvement.